2023
DOI: 10.3390/ijerph20054158
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Validation of the Lithuanian Version of the Sport-Specific Doping Self-Regulatory Efficacy Scale

Abstract: Background: Use of banned performance enhancing substances in sport is one of the most widely recognized anti-doping rules violation. Research evidence suggests that self-regulatory efficiency is one of the key psychosocial processes related with doping. Therefore, aiming to generate more insights on the self-regulatory efficacy, sport-specific doping self-regulatory efficacy scale was proposed. The aim of the present study was to adapt and validate the Lithuanian version of the sport-specific doping self-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…The Sport-Specific Doping Self-Regulatory Efficacy Scale [ 15 , 38 ] adapted to the Lithuanian context [ 39 ] was used to measure athletes’ perceived ability to resist doping. Participants had to express how confident they were in their ability to refrain from using illegal substances to enhance performance in sport by evaluating seven items (e.g., “When most athletes in your sport use them”, and “When pressured to do so by others”) by using a 7-point scale, ranging from 1 ( not at all confident ) to 7 ( completely confident ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sport-Specific Doping Self-Regulatory Efficacy Scale [ 15 , 38 ] adapted to the Lithuanian context [ 39 ] was used to measure athletes’ perceived ability to resist doping. Participants had to express how confident they were in their ability to refrain from using illegal substances to enhance performance in sport by evaluating seven items (e.g., “When most athletes in your sport use them”, and “When pressured to do so by others”) by using a 7-point scale, ranging from 1 ( not at all confident ) to 7 ( completely confident ).…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores reflect a stronger athlete’s perceived ability to refrain from using illegal substances. Previous studies have shown that the reliability of this scale was very good (α = 0.96) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%